The Presidency of Ulysses S. Grant - Calhoun, Charles W. (Charles William), 1948- (Book collections on Project MUSE., 2017)
"This is the 36th volume in the American Presidency Series; it covers the two-term (1868-1877) controversial presidency of Ulysses S. Grant (1822-1885). While several biographies of Grant have appeared in recent years, there has been no scholarly work on Grant's presidency since the 1930s. Charles Calhoun is an eminent authority on the history of the United States in the late nineteenth century, and uses his vast knowledge here, along with extensive use of original sources, to examine Grant's presidency in a fresh light"--